Synaptobrevin/vesicle-associated membrane protein (VAMP) of Aplysia californica: structure and proteolysis by tetanus toxin and botulinal neurotoxins type D and F. - Yamasaki, S (1994)
Synaptobrevin/vesicle-associated membrane protein (VAMP) and syntaxin are potential vesicle donor and target membrane receptors of a docking complex that requires N-ethylmaleimide-sensitive factor (NSF) and soluble NSF-attachment proteins as soluble factors for vesicle fusion with target membranes. Members of this docking complex are the target of clostridial neurotoxins that act as zinc-dependent proteases. Molecular cloning of the Aplysia californica synaptobrevin cDNA revealed a 180-residue polypeptide (M(r), 19,745) with a central transmembrane region and an atypically large C-terminal intravesicular domain. This polypeptide integrates into membranes at both the co- and posttranslational level, as shown by modification of an artificially introduced N-glycosylation site. The soluble and membrane-anchored forms of synaptobrevin are cleaved by the light chains of the botulinal toxins type D and F and by tetanus toxin involving the peptide bonds Lys49-Ile50, Gln48-Lys49, and Gln66-Phe67, respectively. The active center of teh tetanus toxin light chain was identified by site-specific mutagenesis. His233, His237, Glu234, and Glu270/271 are essential to this proteolytic activity. Modification of histidine residues resulted in loss of zinc binding, whereas a replacement of Glu234 only slightly reduced the zinc content.